The Influence of Money-Holding Ethics on the Behavior of Muslim Individuals During the Covid-19 Pandemic - Bayuni, Eva Misfah; Yunus, Muhammad; Muhlishoh, Ai Anisa; Febriana, Fahira; Haq, Mujahid Al; Mujahid, Mujahid (KnE Social Sciences, 2023)
According to an Islamic economic perspective, the ethics of holding money for Muslims encompass acquiring money, limitations on its usage, and its distribution. The COVID-19 pandemic has indirectly impacted people’s attitudes towards holding money. This study aims to elucidate the influence of money-holding ethics on the behavior of Muslim individuals during the pandemic. The findings indicate that the variables of acquiring money and the allocation of its distribution partially affect the behavior of Muslim individuals. However, the variable of limiting the use of money does not exhibit a partial effect on variable Y. Additionally, all variables exert an influence on the behavior of individual Muslims. The coefficient of determination (R Square) in this study is 0.21, indicating that the variables of acquiring money, limiting its use, and allocating its distribution account for 21.1% of the impact on Muslim individuals’ behavior, while the remaining 78.9% is influenced by other variables. Keywords: ethic, money, Muslim’s behavior